Existence and Stability of Steady Waves for the Hasegawa-Mima Equation. (5th March 2009) - Guo, Boling; Huang, Daiwen
Abstract : By introducing a compactness lemma and considering a constrained variational problem, we obtain a setG ℝ 2 of steady waves for Hasegawa-Mima equation, which describes the motion of drift waves in plasma. Moreover, we prove thatG ℝ 2 is a stable set for the initial value problem of the equation, in the sense that a solutionψ ( t ) which starts nearG ℝ 2 will remain near it for all time.